Affective factors and student's learning : the case of two intermediate english i groups at the foreign language Department of the University of El Salvador - Palacios Jorge, Joel Eliazar
The elements that take place in this project are as follow: first, the topic is stated as a brief introduction to give the reader a general idea what this research is about. Then, the general and specific objectives are listed to identify the purpose of this investigation. After that, the justification is presented to describe the importance of this study; second, the theoretical framework is developed to provide deeply information about previous literature that treats this topic in different scenarios. This is divided in three important segments: Humanistic Approach, Affective Filter Theory and Affective Principles; obviously they are supported by different well known authors. Third, the methodology is explained as a simple description of every single step that researchers followed to gather, process, and analyze data. Fourth, results are presented and discussed in order to make more notable findings. Then, conclusions are noted to understand the status of foreign language learning in our current educational system in relation with affective factors. Along with this, some recommendations are suggested to make this study more valuable for teachers and students of the Foreign Language Department at the University of El Salvador.